2018
DOI: 10.1371/journal.pone.0196890
|View full text |Cite
|
Sign up to set email alerts
|

SpTransformer proteins from the purple sea urchin opsonize bacteria, augment phagocytosis, and retard bacterial growth

Abstract: The purple sea urchin, Strongylocentrotus purpuratus, has a complex and robust immune system that is mediated by a number of multi-gene families including the SpTransformer (SpTrf) gene family (formerly Sp185/333). In response to immune challenge from bacteria and various pathogen-associated molecular patterns, the SpTrf genes are up-regulated in sea urchin phagocytes and express a diverse array of SpTrf proteins. We show here that SpTrf proteins from coelomocytes and isolated by nickel affinity (cNi-SpTrf) bi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
49
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(54 citation statements)
references
References 70 publications
5
49
0
Order By: Relevance
“…Coelomocyte proliferation was stimulated by removing 1.5% or 5% (once or twice) of the estimated BV from adult IQ animals by inserting a needle through the peristomial membrane and into the coelomic cavity and aspirating 0.24–3.45 ml of CF depending on animal size and percentage of the BV to deplete. CF (50 μl) was removed from control animals and diluted into an equal volume of an anticoagulant, calcium- and magnesium-free seawater with EDTA and HEPES [CMFSW-EH; 460 mM NaCl, 10.73 mM KCl, 7.06 mM Na 2 SO 4 , 2.38 mM NaHCO 3 , 70 mM EDTA, 20 mM HEPES; pH 7.4 (10, 18)] for the purposes of cell counts. Proliferation was evaluated based on the incorporation of EdU (25 mM in aCF; ThermoFisher), which was injected on day 0 into each animal through the peristomial membrane for final concentration of 0.18 mM based on BV estimates.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…Coelomocyte proliferation was stimulated by removing 1.5% or 5% (once or twice) of the estimated BV from adult IQ animals by inserting a needle through the peristomial membrane and into the coelomic cavity and aspirating 0.24–3.45 ml of CF depending on animal size and percentage of the BV to deplete. CF (50 μl) was removed from control animals and diluted into an equal volume of an anticoagulant, calcium- and magnesium-free seawater with EDTA and HEPES [CMFSW-EH; 460 mM NaCl, 10.73 mM KCl, 7.06 mM Na 2 SO 4 , 2.38 mM NaHCO 3 , 70 mM EDTA, 20 mM HEPES; pH 7.4 (10, 18)] for the purposes of cell counts. Proliferation was evaluated based on the incorporation of EdU (25 mM in aCF; ThermoFisher), which was injected on day 0 into each animal through the peristomial membrane for final concentration of 0.18 mM based on BV estimates.…”
Section: Methodsmentioning
confidence: 99%
“…Coelomocytes (10 5 cells) from IQ sea urchins were centrifuged for 5 min at 1,000 × g at 4°C onto Superfrost Plus slides (Shandon; ThermoScientific) using three-slot chimneys and cytospin slide holders (Eppendorf) as described (10) and cells were fixed for immunofluorescence according to Brockton et al (23). EdU was detected using an Alexa Fluor 555 Click-It EdU Imaging Kit (Invitrogen) according to the manufacturer's protocol.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Matranga et al [19] found elevated red spherula counts in Paracentrotus lividus urchins with spineless lesions covering 10 to 20% of the body whereas mechanical damage is known to increase ceolomocyte number and humoral molecule expression [20]. While many studies have investigated the immune response in sea urchins [21][22][23], few have considered the impact of spine damage on immune function and bacteremia.…”
Section: Introductionmentioning
confidence: 99%